Stability of Exact and Discrete Energy for Non-Fickian Reaction-Diffusion Equations with a Variable Delay - Dongfang Li; Chao Tong; Jinming Wen (Abstract and Applied Analysis)
This paper is concerned with the stability of non-Fickian reaction-diffusion equations with a variable delay. It is shown that the perturbation of the energy function of the continuous problems decays exponentially, which provides a more accurate and convenient way to express the rate of decay of energy. Then, we prove that the proposed numerical methods are sufficient to preserve energy stability of the continuous problems. We end the paper with some numerical experiments on a biological model to confirm the theoretical results.